The structure and procedure of the Shari`ah courts: historical dynamics and some contemporary practices - Haneef, Sayed Sikandar Shah (Ashgate Publisher, 2014)
Islam in order to ensure that equilibrated, balanced and equitable fulfillment of people`s mutual rights and obligations are achieved and henceforth justice, its supreme goal, reigns and prevails, it has enjoined adjudication of disputes among the people. To this end, therefore, the Prophet, through judicial practice and decrees, guided the Ummah as to the process and principles of administering justice in the Islamic setting.